2019
DOI: 10.1051/e3sconf/201910900121
|View full text |Cite
|
Sign up to set email alerts
|

Development of the theory of laying a hoisting rope on the drum of a mining hoisting machine

Abstract: For new designs of mine hoisting machines, the development of scientifically-based solutions to increase the rope capacity and reduce the size of the machines is relevant. Based on the theory of laying the rope on a lined cylindrical drum developed by the authors, it is shown that when choosing a groove profile and winding pitch for a non-lined drum, it is necessary to use a geometric rope laying model, and for taking into account the elastic lining, it is necessary to use a physical model of static interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
0
4
0
5
Order By: Relevance
“…13 shows a schematic diagram of a hydraulic drive of erector devices, which consists of a constant pressure hydraulic pump 0 p ; hydraulic tank; 4-way hydraulic DCV, in which the stroke of the spool ( ) u t depends on time; a double-acting hydraulic cylinder (hereinafter referred to as the hydraulic cylinder) and a material point with a mass M affected by a resistance force r F . For the function of each channel of the spool, under the assumption that the inertia of the liquid is not taken into account, the following formula is valid, which reflects the flow rate of the liquid, the stroke of the spool and the pressure drop in its cavities, namely (8) it follows that the movement of the object is possible only in the case when the applied pressure exceeds the loss of hydraulic resistance, i.e. 1 ( ) 1.…”
Section: Analytical Model Of Hydraulic Drivementioning
confidence: 99%
See 1 more Smart Citation
“…13 shows a schematic diagram of a hydraulic drive of erector devices, which consists of a constant pressure hydraulic pump 0 p ; hydraulic tank; 4-way hydraulic DCV, in which the stroke of the spool ( ) u t depends on time; a double-acting hydraulic cylinder (hereinafter referred to as the hydraulic cylinder) and a material point with a mass M affected by a resistance force r F . For the function of each channel of the spool, under the assumption that the inertia of the liquid is not taken into account, the following formula is valid, which reflects the flow rate of the liquid, the stroke of the spool and the pressure drop in its cavities, namely (8) it follows that the movement of the object is possible only in the case when the applied pressure exceeds the loss of hydraulic resistance, i.e. 1 ( ) 1.…”
Section: Analytical Model Of Hydraulic Drivementioning
confidence: 99%
“…The results of scientific research in the field of mechanics of new designs of mine hoisting machines are also of great practical importance. This concerns the justification of new methods for determining the loads during multilayer winding of a rubber cable [7], including assessing the effect of parameters of a rubber cable on the rigidity of the winding body [8]. Other sources are devoted to the theory of laying a hoisting rope on a drum [9,10], justification of the algorithm for selecting the parameters of the elastic lining of the drums [11], determination of the dependence of dynamic parameters on the parameters of the technical condition of individual units of the installation [12,13], and may be useful in the practice of studying the stress-strain state of drums of mine hoisting machines [14].…”
Section: Introductionmentioning
confidence: 99%
“…In [8], it has been revealed that after cryogenic treatment, the static strength of synthetic diamonds increases, caused by an irreversible change in the initial stress-strain state of the crystals, due to the ordering of the crystal lattice defective structure. In [9][10][11] a fl at model of the interaction of elements (cables) in a composite product is presented through a material binding them, which has excellent mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Величину зносу визначали за формулою: Результати дослідно-промислового випробування футерування з фенол-капрону. На основі вживаної поліамідної тканини була виготовлена і встановлена пружна футеровка з матеріалу фенол-капрон на підйомній машині Ц-3,5×2 [5,6]. Тип підйому -клітковий, діаметр каната 37,5 мм, крок укладання каната -40 мм, максимальний натяг каната становить 10 тс, швидкість підйому 5 м/с, довжина каната 800 м, середнє число циклів підйому 100.…”
unclassified